A novel method to prepare homogeneous biocompatible graphene‐based PDMS composites with enhanced mechanical, thermal and antibacterial properties. (2nd November 2018) - Hu, Xiaodong; Qian, Wei; Li, Xiaochong; Fei, Guoxia; Luo, Gaoxing; Wang, Zhanhua; Xia, Hesheng
Abstract : A negative pressure assisted mixing method was applied to prepare homogeneous graphene‐based polydimethylsiloxane (PDMS) composite. The problem of graphene agglomeration in polymer matrix was well overcome by using the graphene microsphere aerogels. They possess unique porous structure and excellent adsorption capacity, enabling the PDMS solution can uniformly fill into the reduced graphene oxide aerogel microspheres (rGOAMs) or GO aerogel microspheres (GOAMs) under reduced pressure. Raw reduced graphene oxide (rGO) and graphene oxide (GO) were added into PDMS by a simple ultrasonic assisted mixing method as a comparison. rGOAMs‐PDMS and GOAMs‐PDMS composites displayed higher tensile strength, Young's modulus and storage modulus than rGO–PDMS and GO–PDMS composites. In addition, the thermal stability of graphene‐based PDMS composites was also significantly improved. Finally, rGOAMs‐PDMS and GOAMs‐PDMS composites performed much better antibacterial activity than that of rGO‐PDMS and GO‐PDMS composites, which demonstrated that this kind of graphene‐based PDMS composites could display a great potential application in biomedical field. POLYM. COMPOS., 40:E1397–E1406, 2019. © 2018 Society of Plastics Engineers